2014
DOI: 10.6000/1929-4409.2014.03.29
|View full text |Cite
|
Sign up to set email alerts
|

“It’s not easy but it's still possible to be an abstainer here”: Non-Drug Use Among Young Men in a Slum Area in Makassar, Indonesia

Abstract: This qualitative study explores the social context and protective factors that enable young men in a slum area (lorong) in Makassar, Indonesia, to abstain from using drugs. Semi-structured interviews, conducted with fifteen male non-drug users in the lorong showed, despite living in a drug risk environment, non-drug users were involved in neither the drug scene nor street culture. There were two main reasons for this: their employment opportunities, albeit in low paid jobs and the informal economy, and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The focus on retributive measures for drug offences has led to the punishment model of sentencing. Studies have shown that if strong retributive measures are carried out, developing countries in Asia, including Indonesia, are likely to encounter the reproduction of socio-economic problems through the increasing use of imprisonment [24,25]. More recently, studies of sentencing practices for drug-related offences have noted an evolution from retributive to rehabilitative approaches.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on retributive measures for drug offences has led to the punishment model of sentencing. Studies have shown that if strong retributive measures are carried out, developing countries in Asia, including Indonesia, are likely to encounter the reproduction of socio-economic problems through the increasing use of imprisonment [24,25]. More recently, studies of sentencing practices for drug-related offences have noted an evolution from retributive to rehabilitative approaches.…”
Section: Theorymentioning
confidence: 99%
“…Understanding these socio-economic conditions is essential for understanding the differential use of drugs between different social groups in Indonesia. Nasir et al [25] have indicated that the majority of those prosecuted for drug offences in Indonesia live in urban neighbourhoods, although more generally, it is a practice that features across both rural and urban neighbourhoods. The high-level of underemployment among young people is also suggested as a feature of drug use and criminalisation [24].…”
Section: The Indonesian Contextmentioning
confidence: 99%
“…The influence of sunni Islamic values on rehabilitation as judicial decision... (Cecep Mustafa) Young Men in a Slum Area in Makassar, Indonesia. The conception of "rehabilitation" could be outlined merely regarding productive lifestyles and active citizenship of young men drug users in Indonesia (Nasir et al 2014).…”
Section: The Influence Of Sunni Islam On Justicementioning
confidence: 99%
“…It affects the process of trial, which will lead to a quick investigation. To answer the juridical matter about the categorization of minor cases (Mustafa et al, 2020;Nasir et al, 2014), The Supreme Court of Indonesia produced Government regulations/regulation No. 2 of 2012.…”
Section: Introductionmentioning
confidence: 99%